Evaluation of the effect of Vacciniumarctostaphylos L. fruit extract on serum inflammatory biomarkers in adult hyperlipidemic patients: a randomized double-blind placebo-controlled clinical trial - Sedigheh Asgary; Rasool Soltani; Saeide Mirvakili; Nizal Sarrafzadegan (Wolters Kluwer Medknow Publications, 2016)
Atherosclerosis is a chronic inflammatory condition. Many pro-inflammatory factors including interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), C-reactive protein (CRP), and adhesion molecules including intercellular adhesion molecule (ICAM-1) and vascular cell adhesion molecule (VCAM-1) are expressed in atherosclerotic lesions. The plants of genus Vaccinium are rich in anthocyanins with anti-inflammatory effects. This study aimed to evaluate the effects of Vaccinium arctostaphylos fruit extract on the serum level of TNF-α, IL-6, ICAM-1, and VCAM-1 in adult patients with mild hyperlipidemia to detect its possible inhibitory effects on progression of atherosclerosis. In a randomized double-blind placebo-controlled clinical trial, eligible hyperlipidemic patients were randomly and equally divided in to two groups of study drug or placebo control to receive either the Vaccinium extract or placebo capsules, respectively, twice daily for four consecutive weeks. Each drug capsule contained 0.8 mg of anthocyanins. Serum levels of TNF-α, IL-6, ICAM-1, and VCAM-1 were measured before and after the interventions and finally were compared.A total of 8 men and 12 women in drug group as well as 11 men and 9 women in placebo group completed the study (P = 0.527). The use of Vaccinium extract significantly reduced only the IL-6 level (P = 0.037); however, this reduction was not significant compared to placebo (P = 0.062). Consumption of Vaccinium arctostaphylos fruit extract with the dose of 500 mg twice daily did not show any significant effect on serum levels of TNF-α, IL-6, ICAM-1, and VCAM-1 in adult hyperlipidemic patients. However, considering slight decrease in the level of IL-6, ICAM-1, and VCAM-1, the use of higher doses with longer duration might have significant effects on these factors.